2006
DOI: 10.1021/jm060389m
|View full text |Cite
|
Sign up to set email alerts
|

Indenone Derivatives:  A Novel Template for Peroxisome Proliferator-Activated Receptor γ (PPARγ) Agonists

Abstract: Agonists of peroxisome proliferator-activated receptor γ (PPAR γ) are of interest as a treatment for diabetes, which prompted the identification of a new class of non-TZD PPAR γ agonist. Moreover, compound 14c has displayed the most active agonistic activity with an EC50 value of 50 nM, in addition to exhibiting a new binding mode in the X-ray cocrystal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…In addition, Bae et al (2003) demonstrated that TRO induced apoptosis in human hepatoma cell lines via a PPARγ-independent pathway by activating the cell-death related stress-activated protein kinases. Previous studies showed that KR62776 binds to the ligand binding domain of PPARγ in a different mode from that of rosiglitazone, which is a well known PPARγ ligand with a thiazolidinedione structure (Ahn et al, 2006). Since KR62776 showed no or little effect on human hepatoma cells, it is believed that the novel structure of KR62776 might be important for exhibiting the selective inhibitory action on stellate cells without affecting the cells with a hepatic origin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bae et al (2003) demonstrated that TRO induced apoptosis in human hepatoma cell lines via a PPARγ-independent pathway by activating the cell-death related stress-activated protein kinases. Previous studies showed that KR62776 binds to the ligand binding domain of PPARγ in a different mode from that of rosiglitazone, which is a well known PPARγ ligand with a thiazolidinedione structure (Ahn et al, 2006). Since KR62776 showed no or little effect on human hepatoma cells, it is believed that the novel structure of KR62776 might be important for exhibiting the selective inhibitory action on stellate cells without affecting the cells with a hepatic origin.…”
Section: Discussionmentioning
confidence: 99%
“…The indenone scaffold is considered ap rivileged scaffold due to its presence in aw ide range of biologically active natural (pauciflorol F, [17] and euplectin [18] )a nd synthetic molecules including estrogen binding receptors [19] and antimicrobial, [20] antidiabetic [21] and anticancer [22] molecules. Additionally,s everal indenone derivatives have been developed as drug molecules (donepezil as anti-Alzheimer's disease [23] and indacrinone as antihypertensive [24] drugs) or are potential future drugs (indotecan and indimitecan as anticancer, [25] indotecan and AM13-55 as antileishmanial [26] drugs).…”
Section: Introductionmentioning
confidence: 99%
“…Indenone-containing compounds were widely employed as agonists for estrogen receptor 23 and peroxisome proliferator-activated receptor γ (PPARγ). 24 They also has been used as cyclooxygenase-2 (COX-2) 25 and topoisomerase I (Top I) 26 inhibitors and so on . 27 Therefore, incorporation of the SCF3 group into the indenone moiety can lead to novel series of heterocyclic scaffolds and will bring about further advances in the pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%